Myths and legends from Korea: an annotated compendium of ancient and modern materials - Grayson, James Huntley.
This book contains 175 tales drawn equally from the ancient and modern periods of Korea, plus 16 further tales provided for comparative purposes. Nothing else on this scale or depth is available in any western language. Three broad classes of material are included: foundation myths of ancient states and clans, ancient folktales and legends, modern folktales. Each narrative contains information on its source and provenance, and on its folklore type, similarities to folklore types from China, Japan and elsewhere.